Gay Representation in Boy Meets Boy Movie by Daniel Lopez Sanchez - liawijaya, jefry; Anggraeni, Diana; Sigalingging, Bob Morison (SIGEH ELT : Journal of Literature and Linguistics, 2024)
Currently, illicit relationships such as those of same-sex couples have special symbols that they use as their identity. These symbols are created by their community. We can see directly and analyse their community’s symbols through movies. One of them is the gay movie that this research examined, "Boy Meets Boy". This research uses qualitative methods, which are analyzed using Roland Barthes's semiotic theory. This research aims to identify or find gay symbols using Roland Barthes's semiotic theory formulation. This research obtained 3 gay symbols. The symbols obtained is the result of Roland Barthes's semiotic analysis with three meanings, namely denotation, connotation and myth. Denotation is a real (visual) reading of meaning. Connotation is a subjective reading of meaning, while myth is a relationship between meaning and symptoms or phenomena that are believed by many people. The datum is obtained from the scene of non-verbal communication shown by the gay couple in the "Boy Meets Boy" movie. Non-verbal communication in this movie includes physical touch, kissing on the lips, kissing the hair, stealing glances, glances or stares, and intimate relationships. The implications of existing symbols basically do not have any meaning if we do not know the meaning of the symbols. This symbol is closely associated with the LGBTQ+ community. Hopefully, this research can provide knowledge to find out more about this community.